MEDIASI PENDIDIKAN LINTAS AGAMA SEBAGAI METODE PEMBELAJARAN DI PESANTREN NGALAH PASURUAN - Nur Rokhmatulloh (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2023)
The principle of freedom in Islamic Education, especially freedom of culture in religion, is still considered very sacred and even very exclusive, but it is different if the culture in religion is in the Ngalah Islamic boarding school, culture in religion is only a symbol and does not affect one's beliefs, as is the case for non-Muslims entering the mosque. using kopyah, greeting Muslims and so on, even though this culture is Muslim culture, for non-Muslims not the slightest bit their beliefs will shift or change religions.The method in this study used descriptive qualitative methods, with data collection techniques using in-depth interviews, moderate participant observation and documentation while the data analysis technique in the early stages of data display, the second stage of data reduction and the third stage of drawing conclusions.The existence of Islamic boarding schools, mosques, Pancasila halls and print media is only a cultural symbol or a mediation of interfaith education and is not a sacred or exclusive place, because the knowledge of Allah SWT is not limited, but all knowledge must be developed and practiced in the Islamic boarding school, because of this mediation. has become part of the system in the Ngalah Pasuruan Islamic boarding school, because the Islamic boarding school education system is a means in the form of an organizational device created to achieve educational goals that take place in the Ngalah Islamic boarding school, Purwosari Pasuruan.